2013
DOI: 10.1021/ma400584y
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Coumarin Polyesters That Exhibit Cross-Linking and Chain Scission Properties

Abstract: The synthesis and properties of a new class of photoresponsive coumarin polyesters are described. Incorporation of the coumarin chromophore in the polymer chain provides interesting properties such as polymer chain crosslinking upon irradiation at 350 nm and chain un-cross-linking when irradiated at 254 nm. In addition, irradiation at 254 nm also results in polymer chain scission. The cross-linking, uncross-linking, and chain scission properties were studied by ssNMR, ATR-IR, and GPC measurements. These proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 50 publications
3
100
1
1
Order By: Relevance
“…We have previously shown that coumarin polyester films demonstrate this dual photochemistry−undergoing primarily cross-linking at 350 nm and chain scission at 254 nm ( Figure 1). 31 This dual behavior enabled the fabrication of complementary micropatterned surfaces by irradiation at 350 or 254 nm. In this work to clearly understand the reactions, we utilize thin films of the virgin coumarin containing polyester (CA11) and irradiate either at 350 nm to enable polymer crosslinking, or at 254 nm to induce chain scission.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that coumarin polyester films demonstrate this dual photochemistry−undergoing primarily cross-linking at 350 nm and chain scission at 254 nm ( Figure 1). 31 This dual behavior enabled the fabrication of complementary micropatterned surfaces by irradiation at 350 or 254 nm. In this work to clearly understand the reactions, we utilize thin films of the virgin coumarin containing polyester (CA11) and irradiate either at 350 nm to enable polymer crosslinking, or at 254 nm to induce chain scission.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…31 A decrease in the absorbance coefficient, α, is expected for the cross-linked products due to the change from a coumarin chromophore to a benzenoid chromophore after cross-linking. However, chain scission, which is the minor product at 350 nm, is not expected to show a decrease in α because this does not cause a change in the structure of the chromophore.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The synthesis of the monomers and polymer has been described in our earlier publication. 27 In brief, the coumarin polyester CA11 ( Figure 1A) is synthesized by the carbodiimide mediated polymerization of the coumarin diol (250 mg, 1 mmol, 1 equiv) with adipic acid (146 mg, 1 mmol, 1 equiv). The above diol and diacid are taken in an evacuated and N 2 filled round bottomed flask along with 4-(N,Ndimethylamino)pyridinium-4-toluenesulfonate (DPTS, 117 mg, 0.4 mmol, 0.25 equiv) and N,N-diisopropylcarbodiimide (DIC, 470 mL, 3 mmol, 3 equiv).…”
Section: Methodsmentioning
confidence: 99%
“…27 This design enables the polymer to demonstrate dual photoreactive properties. Irradiation at 350-365 nm results in polymer chain crosslinking as a result of a [2 + 2] cycloaddition reaction between the coumarin units.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent irradiation of the coumarin dimer at λ<300 nm induces cleavage of the cyclobutane ring and the monomer coumarins reform. Various coumarin-functionalized polymer materials, in particular, photo-cross-linking polymers have been reported thus far [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Chujo et al reported photocontrollable swelling behavior of hydrogel films obtained from polyoxazoline having a coumarin moiety [1].…”
Section: Introductionmentioning
confidence: 99%